An Evaluation of the Solubility of Four Endodontic Sealers in Different Solvents (An In Vitro Study) - Noor H Fadhil; Majida K Al-Hashimi (College of Dentistry/ University of Baghdad, 2015)
Background: Complete removal of filling material from the root canal is an essential requirement for endodontic retreatment. The purpose of the present study is to evaluate and compare the dissolving capabilities of various solvents (Xylene, Eugenate Desobturator, Eucalyptol, EDTA and Distilled water (as a control)) on four different types of sealer (Endofill, Apexit Plus, AH Plus and EndoSequence bioceramic sealer). Materials and method: Eighty samples of each sealer were prepared according to the manufacturers' instructions and then divided into ten groups (of 8 samples) for immersion in the respective solvents for 2 and 5 min immersion periods. Each sealer specimen was weighed to obtain its initial mass. The specimens were immersed in the tested solvents for 2 and 5 min, followed by rinsing with double distilled water and blotted dry with an absorbent paper, then they were reweighed to determine its final mass. The mean of weight loss was determined for each material in each solvent during the specified immersion period, and the values were subjected to statistical analysis. Results: Clear differences were shown in the solubility profile of these root canal sealers in the tested solvents. The result of the present study shows that Xylene had the greatest capacity for dissolving Endofill, Apexit Plus and AH Plus. Eugenate Desobturator, Eucalyptol and EDTA showed a highly significant dissolving capability on these sealers with variations between these subgroups; EndoSequence BC sealer is insoluble in these tested solvents. Regarding the immersion time, higher values of solubility were obtained at 5 min than that at 2 min immersion time. Conclusion: The results showed that Xylene, Eugenate Desobturator, Eucalyptol and EDTA can be used for the removal of Endofill, Apexit Plus and AH Plus during endodontic retreatment with variations between these subgroups; D.W (control group) showed the least capacity for dissolving these sealers. EndoSequence BC sealer is insoluble in the tested solvents.